Predicting long-term memory via pupillometry - Oria Pitem; Yaniv Mama (Scientific Reports)
Abstract Pupillometry research has established that pupil size reflects cognitive processes through autonomic nervous system activity, with high arousal triggering pupil dilation. Studies examining pupil size during encoding have yielded conflicting results regarding its relationship with subsequent memory performance, and few have investigated baseline pupil size. This study examined whether pupil diameter before and during stimulus presentation predicts memory performance. We hypothesized that successfully recalled words would be associated with larger pupils than forgotten words, based on the role of arousal and attention in memory formation. To test these hypotheses, we conducted two experiments in which we tracked ninety-five psychology students’ eyes while they performed a long-term memory test. The results depict larger pupil size while studying later successfully retrieved words. Interestingly, this phenomenon also occurs before word presentation (during baseline), which supports the “readiness to remember” (R2R) framework. This implies that pupillary changes while preparing to encode information can indicate later memory performance.